Special edition packaging and its negative effects on search and the shopping experience. Issue 2 (2nd April 2020) - Shepherd, Steven; Fitzsimons, Gavan J.
ABSTRACT: Past research offers mixed advice for marketers regarding the benefits of novel packaging. We find that special edition packaging, even when especially visually salient, impedes consumers' search for the target product and leads to more negative evaluations of the shopping experience. Special edition packaging that retains (vs. abandons) familiar brand elements that are used in search (namely, color) attenuates these negative effects. Pre-shopping exposure to the special edition packaging also attenuates these negative effects. Overall, this research highlights the negative impact of deviating from familiar brand cues and the importance of top-down processes in goal-directed searches. Implications are discussed.